School grounds as a place for environmental learning in the life skills learning programme - Mambinja, Sindiswa (Rhodes University, Faculty of Education, Department of Education, 2009)
With the intention of improving my own practice, the study investigated how school grounds could be used for environmental learning in the Foundation Phase Life Skill Learning Programme within the Revised National Curriculum Statement. The research was conducted in the Grade One class of Ntaba Maria Primary School situated in Grahamstown East. The study was an action research case study based on interpretive approach to research. It had two cycles comprised of two lesson plans. The first Lesson Plan focused on an audit of the school grounds to identify environmental issues. The second Lesson Plan was informed by the audit, and addressed one of the identified environmental issues. Data was gathered through analysis of curriculum documents, video recordings and photographs of learning interactions, journal entries and learners' work. The study highlighted that school grounds provided a context for environmental learning within Life Orientation Learning Area especially when integrated with other learning areas. There were cases however, where assessment standards were only partly addressed. The study also revealed that the Life Orientation Learning Area was also limiting for school grounds learning opportunities in some cases. In other cases the study highlighted the open-ended nature of some of its assessment standards. The study also revealed how school grounds related activities offered opportunities and challenges for constructivist, situated and active learning. Opportunities and challenges regarding group work, language use, active engagement with information learning in authentic settings, and action and action competence; emerged as issues from the analysis. Finally, the study shed light on how reflection on learners' work and assessment of these could help teachers modify activities and do them differently so as to enhance the achievement of skills, knowledge, attitudes and values. The achievement of investigative and problem-solving skills through the two lesson plans was critically evaluated as the processes of values education employed in the lesson implementation.
Keywords: Environmental education -- Study and teaching (Elementary) -- South Africa --Grahamstown; Life skills -- Study and teaching (Elementary) -- South Africa Education -- South Africa -- Curricula; Education, Elementary -- South Africa; School grounds -- South Africa -- Grahamstown; Curriculum-based assessment -- South Africa